The Role of Psychological Distress in Gender Differences of Perceived Relaxation within Urban Open Spaces - Dessy Syarlianti; Emmelia Tricia Herliana; Cynthia Puspitasari; Dian Duhita Permata (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
Rapid urbanization has intensified mental health challenges in cities, highlighting the growing importance of urban open spaces as perceived relaxation environments. Although relaxation qualities have been widely examined, conventional assessments frequently generalize user characteristics, overlooking the influence of baseline mental health. Consequently, environmental literature often assumes uniform restorative outcomes, neglecting how psychological distress varies across genders. This study investigates gender differences in perceived relaxation of urban open spaces, with a particular focus on psychological distress. This research conduct a cross-sectional study with a semi-structured online questionnaire involving 101 adult participants. The data of psychological distress was assessed using the World Health Organization's Self-Reporting Questionnaire (SRQ-20). Relevant environmental elements were identified through word-frequency analysis on semi-open-ended description, and then examined using analysis of variance and correspondence analysis. The results indicate that psychological distress has a more direct association with perceived relaxation than gender. While psychological distress influences how individuals perceive the experience, gender differences shape how those experiences are enacted. This study also reveal that natural greenery and coherent spatial design act as primary relaxation elements, whereas facilities and social interaction serve as secondary elements, utilized differently across gender. These findings highlight the importance of incorporating users' internal conditions into the design process to enhance the relaxation potential of urban open spaces. Design approaches must move beyond the uniform assumptions that often characterize current practice in order to create inclusive and relaxing urban environments that support everyday mental well-being.